Developmental psychopathology: recent advances and future challenges. Issue 3 (October 2015) - Pollak, Seth D.
<x xml:space="preserve">Abstract</x> The integrative field of developmental psychopathology is having a huge impact on our understanding of human health and behavior. In this paper, I use the example of children's early stress exposure to illustrate how developmental psychopathologists now tend to deemphasize diagnostic categories and, instead, emphasize the social and biological contexts, events and circumstances that have created opportunities for maladaptive responses and health problems in youth. This example shows that developmental psychopathology is increasing understanding of how children develop the abilities that allow them to cope effectively with challenges and what leads to failures in development of these abilities. Integrating research about the neurobiology of learning may prove to be a powerful future direction to understand how the environment regulates behavior. Learning processes become increasingly intricate and fine‐tuned as relevant neuroanatomical systems develop, and as the range, complexity and amount of environmental information increases for the developing child. A focus on these processes allows psychopathologists to formulate questions about which neural mechanisms children use to process information, how these mechanisms are themselves shaped by social context, why adverse social environments confer risk for children, and, perhaps, what sorts of neutrally informed interventions might remediate the deficits in self‐regulation that underlie common psychopathologies.